PENGARUH TEMAN SEBAYA DALAM PERILAKU SOSIAL REMAJA PADA SISWA SMAN 21 MEDAN - Aiga Nurkhalilah Pasaribu; Putra Apriadi Siregar (JIP: Jurnal Ilmu Pendidikan, 2023)
Each individual conducts social interaction with his environment, children make adjustments to speech styles, appearance styles and even imitate personalities to peers in the surrounding environment. This study used quantitative descriptive method. To determine the influence of peers in adolescent social behavior, especially in grade XI students of SMAN 21 Medan. Friendship factors that influence adolescent social behavior are the first to be influenced by peer friendship, where the results of research on peer influence on adolescent social behavior are 90.6%. Then the second because they have the same hobby by 56.3% and the last because they have different tastes only by 15.6%. The conclusion that researchers can draw in this study is the friendship factor that influences adolescent social behavior due to peer friendship where the results of the study amounted to 90.6%.